Dose-response of neuromuscular and anaerobic performance to whole-body vibration - Núbia Carelli Pereira de Avelar; Daniele Maria Silva Viana; Vanessa Gonçalves César Ribeiro; Fabiano Salvador; Ana Cristina Rodrigues Lacerda (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: The present study was designed to investigate the dose-response relationship of muscular performance and anaerobic power to whole-body vibration (WBV). Methods: Nine recreationally males were subjected to five experimental conditions: A) Squat exercise (SE) without WBV; B) WBV1 [31.55 m.s-2]; C) WBV2 [159.73 m.s-2]; (D) WBV3 [319.45 m.s-2]; and E) WBV4 [567.91 m.s-2]. Before and after the experimental procedures, muscle performance was assessed by a vertical jump test and handgrip strength test and anaerobic power by Wingate anaerobic test (WT). Results: WBV2 and WBV3 increased jump relative power [Δ=0.92 ± 0.89 W/Kg (+1.97%) and Δ=1.29 ±1.79 W/Kg (+2.77%), respectively; P=0.02; effect size= 0.92; power= 0.87] and height [Δ=0.96 ± 0.73 cm (2.80%) and Δ=1.61 ± 2.36 cm (4,57%), respectively; P= < 0.01; effect size= 0.96; power= 0.99] compared to the SE [Δ=-1.28 ± 0.81 cm (-3.55%)]. There was no dose-response relationship of handgrip strength to WBV. WBV2 improved WT relative power (power/body weight) compared to the other experimental conditions [Δ= 0.61 ± 0.36 W/Kg (+ 5.25%); P < 0.01; ; effect size= 0.98; power= 0.99], and WT relative work was higher in WBV3 [Δ= 1.86 ± 5.46 KJ/Kg (+ 0.70%)condition compared to WBV1[Δ= -6.71 ± 4.03 KJ/Kg (- 2.49%) ( P= 0.03). Conclusion: These results suggest that lower limb muscular performance and anaerobic power are responsive to vibration accelerations WBV2 (159.73 m.s-2) and WBV3 (319.45 m.s-2).